Unsettling transdisciplinary perspectives on sustainability issues: A critical discourse (metadata) cross-case analysis. Issue 5 (3rd September 2021) - Sefotho, Maximus Monaheng
Abstract : This study is a critical discourse (metadata) cross-case analysis of six manuscripts on psychology of sustainable development that comprise a special section on transdisciplinary approaches to sustainable development. These six manuscripts span a broad range of topics: the psychology of sustainability, pedagogical knowledge, early literacy, masculinity and gender equality, resilience and workplace requirements, and emotional labour. The analysis yielded the following cross-cutting themes: Socio-emotional well-being, praxis for development, future generations, resourcing for the future, gender and sustainability, and personal resources for sustainability. Evidence suggests that sustainability is not adequately researched and infused in psychology articles. However, a newly emerging paradigm of psychology of sustainable development is well positioned to generate psychology-based research on sustainable development, with implications for new fields of studies.